Experimental investigation on slope runoff, sediment, and hydraulic parameters under different underlying surface - Hamizak, Siti Norhafizah; Suif, Zuliziana; Jelani, Jestin; Ahmad, Nordila; Akhtar, Muhammad Izzul (SINERGI, 2025)
This study utilizes a rainfall simulator to conduct an experimental investigation of slope and rainfall on various underlying surfaces. This study aimed to determine the relationship between various hydraulic factors and sediment concentration by estimating runoff, sediment concentration generation, and hydraulic parameters on various underlying surfaces. The flow velocity, flow depth, shear stress, and unit stream power are the hydraulic parameters in this experiment. The soil sample will be set up appropriately in the rainfall simulator with a slope of 20º and subjected to a rainfall event for two hours on four trays with various underlying surface types. The rainfall intensity of 10 Lmin⁻¹ was designated for the rainfall simulator. Throughout a two-hour period, the runoff flow was collected at intervals of 30, 60, 90, and 120 minutes. The measured sediment concentration using Total Suspended Solid (TSS). Then measurements were conducted of the sediment concentration, runoff discharge, and hydraulic parameters. According to the results, the stream power of the four covers is higher for the dried leaves (0.004606 ms-3), grass cover (0.003274 ms-3), gravel (0.00232 ms-³), and bare soil cover (0.00081 ms-³). But bare soil produces the maximum concentration of sediment and surface runoff, which is then followed by grass, gravel, and leaves. In general, the generation of sediment began with the bare surface, gravel, dry leaves, and grass in descending sequence. Research has shown that rain-induced plant cover can be used as a low-cost strategy to reduce soil erosion on construction slope sites.